Finite element analyses and simulations of sheet metal forming processes - Mackerle, Jaroslav (Engineering computations, 2004)
Sheet metal forming is a process of shaping thin sheets of metal by applying pressure through male or female dies or both. In most of used sheet-formating processes the metal is subjected to primarily tensile or compressive stresses or both. During the last three decades considerable advances have been made in the applications of numerical techniques, especially the finite element methods, to analyze physical phenomena in the field of structural, solid and fluid mechanics as well as to simulate various processes in engineering. These methods are useful because one can use them to find out facts or study the processes in a way that no other tool can accomplish. Finite element methods applied to sheet metal forming are the subjects of this paper. The reason for writing this bibliography is to save time for readers looking for information dealing with sheet metal forming, not having an access to large databases or willingness to spend own time with uncertain information retrieval. This paper is organized into two parts. In the first one, each topic is handled and current trends in the application of finite element techniques are briefly mentioned. The second part, an Appendix, lists papers published in the open literature. More than 900 references to papers, conference proceedings and theses dissertations dealing with subjects that were published in 1995-2003 are listed.